Distributed Nash Equilibrium Seeking for Nonlinear Multiagent Systems Subject to Transmission Outliers With Applications to Satellite Formation System - Zhang, Peng; Yuan, Yuan (IEEE transactions on aerospace and electronic systems, 2025)
This article investigates a distributed outlier-resistant Nash equilibrium (NE) seeking control problem for a class of nonlinear multiagent systems (MASs) under a time-varying network topology. In the MAS, the signals suffer from transmission outliers probably caused by impulsive interference. For the purpose of reducing the negative effects caused by the undesired transmission outliers, two modified stubborn estimators including finite-time graph estimator and state estimator, are designed by using dynamic saturation nonlinear functions. In an effort to find the NE points of the MASs, an auxiliary state variable is applied into the NE seeking control approach. Then, sufficient conditions are given to guarantee that the system states converge into the neighborhood of the NE points. Finally, a typical example on multisatellite formation systems is simulated to validate the effectiveness of the devised NE seeking control strategy.